The 100 classic papers in ulcerative colitis: a bibliometric analysis. (2nd October 2016) - Connelly, Tara M.; Devane, Liam; Kelly, John C.; Wrafter, Paula; Messaris, Evangelos
ABSTRACT: Background : The identification of the top 100 papers in ulcerative colitis (UC) using citation analysis provides a unique insight into the advancement of disease understanding and subsequent treatment innovations that have progressed over time. Methods : The Thomson Reuters Web of Knowledge was used to identify the 100 most cited UC manuscripts. Title, first and senior authors, institution and department of first author, journal, country of origin, year and topic of each manuscript were analyzed. Results : The top 100 manuscripts were published between 1955–2012. Thirty eight percent of the manuscripts originated from the US followed by the UK (26%). Genetics was the topic with the most publications (n = 27), followed by treatment (n = 22) and immunological pathways (n = 17). Truelove had the highest amount of authorships. The institutions with the highest number of publications were St. Mark's, London and the Radcliffe Infirmary. Conclusion : This list of highly cited papers identifies the topics and authors that have made the most impact in the study of UC over the last century. This paper provides a reference of what could be considered as the most influential UC papers and serves as a reference of what comprises a 'highly citable' manuscript for both researchers and clinicians.